Variability of disease activity in patients with hereditary angioedema type 1/2: longitudinal data from the Icatibant Outcome Survey. (5th October 2021) - Maurer, M.; Caballero, T.; Aberer, W.; Zanichelli, A.; Bouillet, L.; Bygum, A.; Grumach, A.S.; Botha, J.; Andresen, I.; Longhurst, H.J.; ,
Abstract: Background: Hereditary angioedema due to C1 inhibitor deficiency (HAE‐1/2) is a chronic and debilitating disease. The unpredictable clinical course represents a significant patient burden. Objective: To analyse longitudinal registry data from the Icatibant Outcome Survey (IOS) in order to characterize temporal changes in disease activity in patients with HAE‐1/2. Methods: Icatibant Outcome Survey (NCT01034969) is an international observational registry monitoring the clinical outcomes of patients eligible for icatibant treatment. The current analyses are based on data collected between July 2009 and July 2019. Retrospective data for attacks recorded in the 12 months prior to IOS enrolment and for each 12‐month period up to 7 years were analysed. Results: Included patients reported angioedema attacks without long‐term prophylaxis (LTP; n  = 315) and with LTP ( n  = 292) use at the time of attack onset. Androgens were the most frequently used LTP option (80.8%). At the population level, regardless of LTP use, most patients (52–80%) reporting <5 attacks in Year 1 continued experiencing this rate; similarly, many patients (25–76%) who reported high attack frequency continued reporting ≥10 attacks/year. However, year on year, 31–51% of patients experienced notable changes (increase/decrease of ≥5 attacks) in annual attack frequency. Of patients who reported an absolute change of ≥10 attacks from Year 1 to 2, 17–50% continued to experience a change of this magnitude in subsequent years. Conclusion: At the population level, attack frequency was generally consistent over 7 years. At the small group level, 28.8–34.5% of patients reported a change in attack frequency of ≥5 attacks from Year 1 to Year 2; up to half of these patients continued to experience this magnitude of variation in disease activity in later years, reflecting high intra‐patient variability.